Unveiling Lintang's Resilience and Grit: An Appraisal Analysis of 'Tenacity', 'Capacity', and 'Normality' in Laskar Pelangi - Dewi Cahyaningrum; Djatmika, Djatmika (Universitas Cokroaminoto Palopo, 2024)
This study aims to analyze how language is used to portray Lintang as a resilient and gritty character in the novel Laskar Pelangi, through the theoretical framework of Systemic Functional Linguistics (SFL) and drawing on Martin and White’s (2005) Appraisal theory. The specific objective of this research is to explore how linguistic choices in the novel construct the character of Lintang in terms of his resilience and grit, focusing on the aspects of judgment, particularly tenacity, capacity, and normality. The method used in this study involves a qualitative analysis of textual evidence from the novel. Linguistic elements related to judgment are identified, categorized, and analyzed based on their contribution to portraying Lintang’s resilience and grit. The findings of this study reveal that Lintang's character is constructed through a combination of linguistic elements that emphasize his extraordinary tenacity, strong capacity, and relatable normality. Despite being frequently underestimated due to his simple physical appearance, these linguistic choices underscore his resilience and grit. Lintang’s ability to overcome societal prejudices and physical limitations highlights the message that true success comes from inner strength and persistence. By illustrating Lintang's journey, Hirata effectively conveys that physical appearance does not define one's potential for greatness. This research contributes to the understanding of how literary characters can inspire resilience and grit in readers, providing valuable insights into storytelling methods that emphasize character development through language.